2012
DOI: 10.1017/prp.2012.10
|View full text |Cite
|
Sign up to set email alerts
|

Equality, Justice and Identity in an Expatriate/Local Setting: Which Human Factors Enable Empowerment of Filipino Aid Workers?

Abstract: This study explored which of social dominance, social identity and perceptions of organisational justice were most predictive of self-reported empowerment among aid workers in the Philippines (N = 98). Responses to an online survey available in English and Tagalog were obtained from employees of diverse locally operating aid organisations in the Philippines. The survey included composite measures of empowerment, perceived social dominance, social identity and organisational justice. All measures except perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
(145 reference statements)
0
3
0
Order By: Relevance
“…According to the humanistic management literature, there are at least two senses in which pay levels can enhance sense of workplace justice and fairness (Furnham 2012;Seth and Alkire 2014): compared to fellow workers, for example, in a similar job or sector (Smith 2012); and compared to management and executives within the same employing organization (Carr 2010a, b;ILO 2013). Both absolute and relative wage levels are linked to perceived justice and fairness at work (Card et al 2012;Mumford and Smith 2012).…”
Section: Anti-poverty Capabilitymentioning
confidence: 99%
“…According to the humanistic management literature, there are at least two senses in which pay levels can enhance sense of workplace justice and fairness (Furnham 2012;Seth and Alkire 2014): compared to fellow workers, for example, in a similar job or sector (Smith 2012); and compared to management and executives within the same employing organization (Carr 2010a, b;ILO 2013). Both absolute and relative wage levels are linked to perceived justice and fairness at work (Card et al 2012;Mumford and Smith 2012).…”
Section: Anti-poverty Capabilitymentioning
confidence: 99%
“…This was done to clarify the role of identity-based information incorporated in organizational justice (Lipponen et al, 2011 ), as well as the mediating role of work identity in relation to the effects of organizational justice on different outcomes (Olkkonen and Lipponen, 2006 ; Cho and Treadway, 2011 ; He et al, 2014 ). Finally, interaction effects of social identity and organizational justice dimensions on different work-related outcomes have additionally been investigated (Cremer, 2006 ; Lipponen et al, 2011 ; Smith, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, Selmer (2000) showed that Swedish (expatriate) bosses in Hong Kong could recognize only one third of locals' contributions to their respective workgroups. As several humanitarian field reports highlight (Alcayna & Al-Murani, 2016;Bjerneld, Lindmark, Garrett, & Diskett, 2004;Da Costa, 2012;McWha, 2011;Shevchenko & Fox, 2008;Vaughan-Smith, 2012), these problems may emerge even more acutely in the aid context due to the various differences between expatriate and local aid workers. As a result, they may be less willing to collaborate.…”
Section: Collaboration Between Local and Expatriate Staff In Humanimentioning
confidence: 99%